2018
DOI: 10.1111/risa.13113
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐Part Bayesian Network for Modeling Dwelling Fires and Their Impact upon People and Property

Abstract: In the United Kingdom, dwelling fires are responsible for the majority of all fire-related fatalities. The development of these incidents involves the interaction of a multitude of variables that combine in many different ways. Consequently, assessment of dwelling fire risk can be complex, which often results in ambiguity during fire safety planning and decision making. In this article, a three-part Bayesian network model is proposed to study dwelling fires from ignition through to extinguishment in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
(64 reference statements)
1
12
0
Order By: Relevance
“…Combining this with the general actual situation of tourism scenic spots and reference to the prior related studies [66][67][68], we establish a fire safety evaluation index system as shown in Table 2. As we can see, the system is a hierarchical structure, including the target level, the base level, and the criteria level.…”
Section: Establishing the Evaluation Indexmentioning
confidence: 99%
“…Combining this with the general actual situation of tourism scenic spots and reference to the prior related studies [66][67][68], we establish a fire safety evaluation index system as shown in Table 2. As we can see, the system is a hierarchical structure, including the target level, the base level, and the criteria level.…”
Section: Establishing the Evaluation Indexmentioning
confidence: 99%
“…Bayesian Networks (BN) are also applied to dwelling fires in [33]. In particular, a three-part BN model is developed to study dwelling fires and improve confidence in dwelling fire safety assessment.…”
Section: B Machine Learning Applied To Fire Datasetsmentioning
confidence: 99%
“…(1) Setting prior probability Firstly, it is necessary to estimate the prior probability of 63 leaf nodes(input nodes). The prior probability in this paper came from fire data analysis, expert knowledge, and on-site sampling statistics of urban buildings over the past years [9,11,13,20]. As shown in figure 5, the node ClosedDoorAnd-Window shows that normally fireprevention doors and windows should be closed during fire inspection.…”
Section: ) Determine Network Parametersmentioning
confidence: 99%
“…Zhang et al [10] propose a Bayesian network analysis model of the fire in the dormitory of colleges and universities, establish a relevant index system, build a Bayesian model for fire risk analysis. Matellini et al [11] represent a three-part BN to simulate the different stages of ordinary residential fires from fire to extinguish. Liu et al [12] construct a BN model to predict the fire risk of urban buildings to calculate the probability of building fires.…”
Section: Introductionmentioning
confidence: 99%